PPARα exacerbates necroptosis, leading to increased mortality in postinfluenza bacterial superinfection - Tam, Vincent C. (Proc Natl Acad Sci U S A, 2020)
Patients infected with influenza are at high risk of secondary bacterial infection, which is a major proximate cause of morbidity and mortality. We have shown that in mice, prior infection with influenza results in increased inflammation and mortality upon Staphylococcus aureus infection, recapitulating the human disease. Lipidomic profiling of the lungs of superinfected mice revealed an increase in CYP450 metabolites during lethal superinfection. These lipids are endogenous ligands for the nuclear receptor PPARα, and we demonstrate that Ppara(−/−) mice are less susceptible to superinfection than wild-type mice. PPARα is an inhibitor of NFκB activation, and transcriptional profiling of cells isolated by bronchoalveolar lavage confirmed that influenza infection inhibits NFκB, thereby dampening proinflammatory and prosurvival signals. Furthermore, network analysis indicated an increase in necrotic cell death in the lungs of superinfected mice compared to mice infected with S. aureus alone. Consistent with this, we observed reduced NFκB-mediated inflammation and cell survival signaling in cells isolated from the lungs of superinfected mice. The kinase RIPK3 is required to induce necrotic cell death and is strongly induced in cells isolated from the lungs of superinfected mice compared to mice infected with S. aureus alone. Genetic and pharmacological perturbations demonstrated that PPARα mediates RIPK3-dependent necroptosis and that this pathway plays a central role in mortality following superinfection. Thus, we have identified a molecular circuit in which infection with influenza induces CYP450 metabolites that activate PPARα, leading to increased necrotic cell death in the lung which correlates with the excess mortality observed in superinfection.